AMS 14C Dating Problem and High-Resolution Geochemical Record in Manzherok Lake Sediment Core From Siberia: Climatic and Environmental Reconstruction for Northwest Altai Over the Past 1,500 Years - Tatiana Blyakharchuk; Valerii Udachin; Hong-Chun Li; Hong-Chun Li; Su-Chen Kang (Frontiers in Earth Science, 2020)
This study presents high-resolution multi-proxy biological and geochemical records in an 82-cm sediment core from Manzherok Lake located in a forest–steppe zone on the western piedmonts of Altai Mountain, Russia. Based on 210Pb dating and 48 accelerator mass spectrometry 14C dates as well as pollen data and geochemical proxies, detailed lake history and local climatic changes over 1,500 years are obtained. Prior to the Medieval Warm Period (MWP), the lake had high productivity under stable moderately wet and warm conditions. During 1,150–1,070 year BP, strong surface runoff led to a high detritus input and an increasing lake level, reflecting the onset of MWP. The lake was deep and fresh under the warm and wet conditions of MWP (1,070–850 year BP). In this interval, more aquatic algae and submerged plants on the lake bottom were generated, which would use dissolved CO2 partially decomposed from organic matters in the deeper sediment layers. Consequently, many acid–base–acid-treated samples contain old carbon influence on their 14C dates. This calls for attention on the chronological construction of lake sediments. During 850–700 year BP, the lake level started to drop with reduced sediment load under cooling and drying conditions. Low sedimentation and lake productivity occurred due to cold and dry climates during 700–500 years BP. Very low sedimentation and hiatus were attributed to ice cover and weak water input between 500 and 50 years BP, corresponding to cold and dry Little Ice Age. Manzherok Lake has recovered productivity and deposition during the current warming century. Change in the total solar irradiance (TSI) is an important factor to influence the climate in the Altai Mountains. With decreased TSI, the Siberian High became strong, which led to the Westerly and the polar front being pushed away from this region, resulting in arid climates. The situation was reversed vice versa.